2011
DOI: 10.5402/2011/374807
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Reinforced High-Performance Concrete Beams Made with Steel Slag Coarse Aggregate

Abstract: In recent years, an emerging technology termed high-performance concrete (HPC) has become popular in construction industry. The constituent materials of HPC depend on the desired characteristics and the availability of suitable local economic alternatives. One of these alternatives is steel slag waste material. It is an industrial by-product waste particles resulted from reinforcing steel bars manufacture, its production is very huge; total quantity produced from all steel rebars manufacture factories in Egypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Figure 8 (a)-(e) demonstrates the cracking pattern of all RC beams that have been tested at failure. After failure, each beams revealed distinctive flexural behavior and no horizontal cracks noticeable at the level of reinforcement, indicating that no bond failure occurred (Zaki et al, 2011). At the commencement of the test, when the load was increasing linearly, there were no cracks.…”
Section: Failure Modesmentioning
confidence: 95%
See 2 more Smart Citations
“…Figure 8 (a)-(e) demonstrates the cracking pattern of all RC beams that have been tested at failure. After failure, each beams revealed distinctive flexural behavior and no horizontal cracks noticeable at the level of reinforcement, indicating that no bond failure occurred (Zaki et al, 2011). At the commencement of the test, when the load was increasing linearly, there were no cracks.…”
Section: Failure Modesmentioning
confidence: 95%
“…Numerous investigations on the flexural behavior of reinforced concrete beams manufactured with alternate CA have been conducted (Mohammed et al, 2017;Raju and Dharmar, 2019;Zaki et al, 2011;Seara-Paz et al, 2018;Yang et al, 2020;Sunayana and Barai, 2018). In this research paper, very few literature studies about flexural behavior of RC beams made with alternative CA has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this juncture, the shear force shifted increasingly onto the longitudinal reinforcement, resulting in a marked increase in the number and width of cracks in the shear span section, as well as in deflection values. Continual loading up to the beam's maximum bearing capacity was accompanied by distinct sounds, culminating in the main diagonal crack forming the final failure surface and localized concrete crushing, ultimately leading to the specimen's failure [27,28].…”
Section: Experimental Validationmentioning
confidence: 99%
“…Numerous studies have been conducted on material characteristics of high-performance concrete (HPC). Recently, use of industry products to construct reinforced HPC has garnered a lot of interest among researchers [1,2]. Effective and reliable force transfer between steel reinforcing bars and concrete is necessary for reinforced concrete buildings to be designed as efficiently as possible [3].…”
Section: Introductionmentioning
confidence: 99%